DC-field-driven combustion waves for one-step fabrication of reduced manganese oxide/multi-walled carbon nanotube hybrid nanostructures as high-performance supercapacitor electrodes. Issue 47 (20th November 2017) - Yeo, Taehan; Shin, Dongjoon; Shin, Jungho; Hwang, Hayoung; Seo, Byungseok; Lee, Jaeho; Choi, Wonjoon
Abstract : DC field-driven combustion waves enable one-step fabrication of heterogeneously reduced, nanostructured electrodes for high-performance supercapacitors. Abstract : Micro–nanostructured metal oxides can facilitate the development of electrochemical electrodes with enhanced features for supercapacitors and batteries. However, the fabrication of electrodes using precisely controlled metal oxides generally requires high-cost, multi-step procedures, which limits the scalability. Herein, we report that a direct current-field-driven combustion wave (DC-CW) enables the one-step fabrication of high-performance supercapacitor electrodes from hybrid nanostructures comprising reduced manganese oxides and multi-walled carbon nanotubes (MWCNTs). A layered film of MnO2 nanoparticles (NPs) and MWCNTs on a nitrocellulose membrane is prepared and subsequently subjected to a DC-electric field, thereby igniting and propagating CWs throughout the film surface within one second. The underlying mechanism of the DC-CW process is elucidated by comparative analysis of the electrodes generated by the laser irradiation-driven combustion wave process without the DC-field and the as-prepared MnO2 /MWCNT film. The Mn x O y /MWCNT hybrids via DC-CWs exhibit higher specific capacitance (757 F g −1 ) and capacitance retention (100%) than the other two systems over 10 000 charge–discharge cycles, due to the improved inter-conductivity and substantial contact interfaces in heterogeneously mixed, less agglomerated nanostructures. The DC-CWs may enable various manipulation methods of micro–nanostructured metal oxides and their hybrid structures via a low-cost, fast, and scalable process for high-performance electrochemical electrodes.